Optimization of Excitation in FDTD Method and Corresponding Source Modeling - Dimitrijevic, Bojan; Nikolic, Bojana; Aleksic, Slavoljub; Raicevic, Nebojsa (Společnost pro radioelektronické inženýrství, 2015)
Source and excitation modeling in FDTD formulation has a significant impact on the method performance and the required simulation time. Since the abrupt source introduction yields intensive numerical variations in whole computational domain, a generally accepted solution is to slowly introduce the source, using appropriate shaping functions in time. The main goal of the optimization presented in this paper is to find balance between two opposite demands: minimal required computation time and acceptable degradation of simulation performance. Reducing the time necessary for source activation and deactivation is an important issue, especially in design of microwave structures, when the simulation is intensively repeated in the process of device parameter optimization. Here proposed optimized source models are realized and tested within an own developed FDTD simulation environment.
Keywords: Finite difference time domain; source modeling; excitation; optimization